Reward Caring with Education, not Condemnation - Fox, Wendy (Wildlife Rehabilitation Bulletin, 2006)
Recently the popular morning talk show Live with Regis & Kelly, seen by four to six million people nationwide each day, showed Kelly caring for a baby robin she had found. She had the bird in a shoebox and was feeding it bread and milk. The immediate concern of the rehabilitation community was obvious; millions of people had now seen a celebrity ‛instructing’ the public on how to raise a baby bird. On behalf of NWRA I spoke with Live and was given the following information: the bird was transferred to a rehabilitator, they spoke with USFWS and NY State for information on regulations, and they were inundated with phone calls and faxes from rehabilitators and concerned members of the public. The following day they corrected the information.